I need to solve d/dx(e^(-(x^2))*(du/dx))=u+x*(du/dx)(adsbygoogle = window.adsbygoogle || []).push({});

I get e^(-(x^2))*u''-2xe^(-(x^2))*u'=u+x*u'

u''-2x*u'=e^(x^2)*u+xe^(x^2)*u'

u''+(2x-xe^(x^2))*u'-e^(x^2)*u=0

but I have no idea how to approach the problem from here. Can somebody please help?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# General Solution to Linear, Homogenius, Second-Order Differential Equation

**Physics Forums | Science Articles, Homework Help, Discussion**